Efficiency and effectiveness video on demand over worldwide interoperability for microwave access - Muthanna Jaafar Abbas; Abeer Abd Al Hameed Mahmood (Institute of Advanced Engineering and Science, 2019)
(WiMAX) is another solution for readiness broadband networks inside the region, covered or not, by alternative technologies like (ADSL) or cable through this paper by deploying many mobility patterns such as static, random and path for Video on Demand (VoD) over (WiMAX) Network. The performance of varied (QPSK) and (QAM) modulation techniques, by applying the (OPNET) simulator version 17.5. This work is finished in terms of the transmitted traffic and received traffic. Simulation result indicates that once nodes are moving by (SVC) code schema in (WiMAX). The result is an effective and attainable overall performance of (QPSK) which is better than (QAM) modulation technique.